Authoritarian Leadership Style Model, Job Burnout and Work Discipline in Improving Performance - Yuni Asmara; Didin Hikmah Perkasa; Nur Vitriani; Ryani Dhyan Parashakti; Wenny Desty Febrian (Fakultas Ekonomi & Bisnis Universitas Paramadina, 2025)
This study aims to determine the effect of authoritarian leadership style, job burnout and work discipline on employee performance at PT Indomarco Prismatama Jakarta 2 Branch. The research design uses casual quantitative methods. Respondents of this study were 65 employees at PT Indomarco Prismatama Jakarta 2 Branch. The data processing tool used is Smart-PLS (Partial Least Square) through outer model testing, inner model and hypothesis testing. The results showed that Authoritarian Leadership had no significant effect on employee performance. However, Job Burnout and Work Discipline have a positive and significant influence on Employee Performance at (PT. Indomarco Prismatama Jakarta 2 Branch). These findings highlight the importance of paying attention to factors such as Job Burnout and Work Discipline in improving employee performance. Management can use the results of this study to develop more effective strategies and policies in improving employee performance in their work environment.